Influence of water-to-geopolymer solids ratio and curing time on the properties of self-compacting geopolymer concrete - Nuruddin, M.F. (Construction Research Institute of Malaysia, 2015)
This paper describes an experimental study that measures the effects of water-to-geopolymer solids ratio on the workability and curing time on compressive strength of self-compacting geopolymer concrete (SCGC). SCGC were synthesized from low calcium fly ash, activated by combinations of sodium hydroxide and sodium silicate solutions, and by incorporation of superplasticizer for self compactability. The experiments were conducted by varying the amount of water and curing time. The water-to-geopolymer solids ratios were 0.31, 0.33, 0.35, and 0.39 and the curing times were 24, 48, 72 and 96 hrs. The effects of water-to-geopolymer solids ratio on workability properties such as filling ability, passing ability and resistance to segregation were assessed through Slump flow, V-funnel L-box and J-Ring test methods. Results showed that the workability was improved with the increase in water-to-geopolymer solids ratio; however, compressive strength was decreased as the ratio of water-to-geopolymer solids by mass increased. An increase in strength was also observed with the increase in curing time from 24 hr to 96 hrs. However, the increase in strength after 48 hrs was not significant. The compressive strength of 53.80 MPa was obtained for SCGC with water-to-geopolymer solids ratio of 0.33 and cured for 48 hrs.